Multimedia Interaktif Tipe Adobe Flash CS6 Berbasis Kurikulum 2013 Dalam Meningkatkan Literasi Verbal Siswa Sekolah Dasar - Dwi agus setiawan; Nur Kumala, Farida (Universitas Nusantara PGRI Kediri, 2020)
Interactive Multimedia Adobe Flash CS6 is a computer-based interactive learning media that is packaged in a CD (Compact Disk) in which there is an interactive application and also has a menu component that can be clicked on to display certain information in it. This interactive multimedia uses the 2013 curriculum as a guide in packaging interactive learning by increasing the verbal literacy of elementary school students. This research and development aims to (1) Produce a product in the form of interactive multimedia based on learning 2013 using Adobe flas CS6 software. (2) Knowing the feasibility of interactive curriculum-based multimedia 2013. 3) Knowing student responses to interactive learning multimedia type Adobe Flash CS6-based learning curriculum 2013 in improving verbal literacy of elementary school students. This research method uses the Research and Development (R&D) method by adopting the ADDIE model which includes: analysis which is conducting curriculum analysis, needs analysis, material analysis; design includes gathering material and questions, display design, story board, components; development, namely media creation and expert validation; implementation of product trials; Evaluation is a discussion of the product after the trial. The research instrument used was observation, interviews, documentation and questionnaires. The data analysis technique used is descriptive analysis of percentages. Research data from limited field trials amounted to 6 students with a percentage of 83.3% with the category